Design and validation of research capability test for educators - Amanonce, Jay-cen Tamayo; Vecaldo, Rudolf Tamangen; Malana, Maribel Fontiveros; Temporal, Conchita Malenab; Tamayao, Antonio Ingaran; Calubaquib, Jhoanna Battung; Calanoga, Marie Claudette Maramag; Tamayo, Ria Arellano (International Journal of Evaluation and Research in Education (IJERE), 2024)
Assessing the research capability of educators yields implications for bridging the gap and addressing concerns along research. Accordingly, the Commission on Higher Education (CHED) highlighted substantive research concerns which need to be given attention specifically in enhancing research capabilities of graduate students, research staff, and faculty which calls for a well-designed and validated research capability test (RCT). Thus, this study established the RCT’s validity and reliability to gauge the knowledge of educators in conceptualizing, implementing, and publishing research. The developed RCT underwent series of critiquing, content validation from experts, and internal and external pilot testing. The study has generated 80 items with desirable difficulty index (50.76), reasonably good discrimination index (0.28), and large functioning distractors (78.97% distractor efficiency). Remarkably, there is a significant association between distractor efficiency and difficulty index of the items with an inter-item consistency of α=0.904. Thus, the RCT is a valid and reliable instrument to gauge the research capability of educators.